Stroke parameter relationships in a repeated swim interval training set - Barden, J. M.; Rorke, S. C. (Medicine & Science in Sports & Exercise, 1999)
This study analyzed velocity, stroke rate, and stroke length parameters in each competitive swimming stroke within an interval set. Ss (M = 2; F = 6) performed eight maximal, push start, 50-m sprint swims three times during a competitive season. Starting intervals were consistent within each testing bout (80 s in test 1, 70 s in tests 2 and 3). Swimming characteristics were video recorded in the 5-m mid-zone of each 25-m swimming length. Velocity and stroke rate decreased significantly within each 50-m sprint, the second 25 m being slower. There was no alteration in stroke length within the full sprint. There was no difference in characteristics across all sets across time. Changes in swimming velocity only affected stroke rate, not stroke length. Decreased stroke rate might serve as a useful indicator of loss of anaerobic power. Implication: Anaerobic fatigue affects swimming velocity and stroke rate, not stroke length.